EVALUASI TERHADAP IMPLEMENTASI PENDIDIKAN KARAKTER DENGAN SISTEM FULL DAY SCHOOL PADA MADRASAHI BTIDAIYAH NEGERI AL AZHAR ASY SYARIF INDONESIA - Madjid Latief, Abdul (Prosiding Seminar Nasional Berseri, 2018)
The aims of this study are (1) to explore the effectivy of character education at Al Azhar Asy Syarif Indonesia Government Elementary School; (2) to explore the factors which support of character education at Al Azhar Asy Syarif Indonesia Government Elementary Schoolof character education at Al Azhar Asy Syarif Indonesia Government Elementary School; (3) to explore the factors which obstacle of character education at Al Azhar Asy Syarif Indonesia Government Elementary School.of character education at Al Azhar Asy Syarif Indonesia Government Elementary School; and (4) to explore the efforts to strength character education at Al Azhar Asy Syarif Indonesia Government Elementary School. This evaluation research used CIPP (Context, Input, Process, Product) model. The data collected by interview, observation, and documentation. Informans consist of headmaster of Al Azhar Asy Syarif Indonesia Government Elementary School, teachers, students, student`s parents, and instuctur of extracuriculum activityAl Azhar Asy Syarif Indonesia Government Elementary Schoolwith. Data analysis was performed data reduction, data representation, making decision and verification. The research shows Al Azhar Asy Syarif Indonesia Government Elementary School had run character education, and match with government policy. And the reseach shows full day system at Al Azhar Asy Syarif Indonesia Government Elementary School make the character education process run better